REPRESENTASI AKTIVITAS PEREMPUAN "MANUMBUAK PADI" DALAM KARYA LUKIS EVELYNA DIANITA - Sari, Nani Dian; Asril, Asril; Munaf, Yuniarti (Studi Budaya Nusantara, 2021)
This paper discusses the Representation of the Minangkabau Women's Activity " Manumbuak Padi" in Evelyna Dianita's painting. Evelyna is a female painter who presents the themes of activities and roles of Minangkabau women such as women's daily activities, women in rituals, women in markets, women in the rural realm and women in kaba / stories. This became the identity of his work as a female painter who was born and grew up in Minangkabau. This article aims to discuss Evelyna's work entitled manumbuak padi from a semiotic perspective. Manumbuak Padi is a form of collaborative activities carried out by Minangakabau women in the gadang home yard, this traditional activity for the Minangkabau community aims to separate rice from its skin. This study uses a qualitative method that passes observations, interviews, documentation and data analysis. Based on the results of the analysis that Evelyna's anxiety about the habit of pounding rice in the traditional way in the Minangkabau community had begun to fade, which was replaced by advanced technology such as helers. This feeling can be seen in the meaning of the sky color symbol that is presented by Evelyna in her work. The writing about Evelyna Dianita's paintings is expected to be a reference, so that there are opportunities for other researchers to examine from different perspectives and sciences.